Screening for sugarcane yellow leaf virus in sorghum in Florida revealed its occurrence in mixed infections with sugarcane mosaic virus and a new marafivirus. (January 2021) - Boukari, Wardatou; Mollov, Dimitre; Wei, Chunyan; Tang, Lihua; Grinstead, Samuel; Tahir, Muhammad Nouman; Mulandesa, Eva; Hincapie, Martha; Beiriger, Robert; Rott, Philippe
Abstract: Sugarcane yellow leaf virus (SCYLV) is an aphid-transmitted virus for which Melanaphis sacchari is the main vector. Almost all sugarcane varieties grown in Florida are susceptible to SCYLV infection. In this study, we investigated the prevalence of SCYLV in accessions of Sorghum bicolor which is another natural host of this virus. Two field experiments, one in 2016 with 19 sorghum lines and the other in 2017 with 15 lines, were established at Belle Glade, FL. Stalks collected randomly in planted and ratoon crops were tested by tissue-blot immunoassay (TBIA) and reverse transcription-polymerase chain reaction (RT-PCR). Over the two-year period, 366 of 423 S. bicolor samples tested positive by TBIA but SCYLV was detected by RT-PCR in only 12 of 161 randomly selected subsamples. Full genome sequences of SCYLV, sugarcane mosaic virus (SCMV) and a new marafivirus were obtained by high-throughput sequencing (HTS) from three TBIA positive sorghum samples. HTS data for all three viruses were confirmed by RT-PCR. The SCMV isolates from S. bicolor appeared to be a new strain of this virus species. Positive reaction of S. bicolor by TBIA using SCYLV antibodies could not be systematically associated with plant infection by SCYLV or another virus. This suggested the occurrence of a non-specific serological reaction with an unknown S. bicolor antigen. SCMV and the new marafivirus were also detected in Sorghum almum, suggesting that this weed is a reservoir for S. bicolor -infecting viruses in Florida. Highlights: Sorghum bicolor lines were colonized by Melanaphis sacchari in south Florida. Prevalence of sugarcane yellow leaf virus was low in Sorghum bicolor. Mixed virus infections occurred in Sorghum bicolor and Sorghum almum. A new marafivirus infecting sorghum in Florida was discovered. The weed Sorghum almum appeared to be a source for sorghum-infecting viruses.